Excess costs of depression among a population-based older adults with chronic diseases in Singapore - Jia Wei Neo; Xue Ying Guo; Edimansyah Abdin; Janhavi Ajit Vaingankar; Siow Ann Chong; Mythily Subramaniam; Cynthia Chen (BMC, 2024)
Abstract Background There is limited evidence on the economic burden of depression among the older population in Singapore. Objective We aim to evaluate the impact of depression on healthcare expenditure and productivity loss among older adults with chronic diseases in Singapore. Methods Using the data from the Well-being of the Singapore Elderly study (WiSE), a 2011 national representative survey of older adults aged 60 years and above, 2510 respondents were included in this study. The sample comprised 44% male and 56% female respondents with 75% respondents aged between 60 and 74 years old. Healthcare utilisation data was obtained from respondents and healthcare cost was tabulated by multiplying each service unit by the unit cost price. These services include care from polyclinic doctors, private general practitioners (GP), outpatient specialists and inpatient care. We modelled the relationship of healthcare cost and depression using two-part models (probit & generalised linear model - loglink and gamma distribution). Results For total healthcare expenditure, older adults with both depression and chronic diseases were associated with an average annual incremental cost of $7940 (95% CI 1490-14400; p = 0.016), compared to those without these conditions. They were also associated with an average incremental cost of $257 (95% CI 38.7-475; p = 0.021) for primary care. Likewise, in the case of specialist outpatient clinics, they had an average incremental cost of $970 (95% CI 163-1780; p = 0.018). However, for inpatient setting, the average incremental cost of $6180 (95% CI 418-12800; p = 0.066) was not significant. Additionally, older adults with depression and chronic diseases contribute to an annual productivity loss of $676 (95% CI 346-1010; p < 0.001). Discussion This study provides evidence that there are significant incremental costs associated with depression amongst the older adults with chronic diseases in Singapore's primary healthcare setting. The increased somatic presentations among the depressed older adults and the underdiagnosis of depression in primary care may contribute to higher utilisation of healthcare resources which entail higher expenditure. This is one of the first studies to look at the cost of depression using a representative sample of Singaporean older adults and taking into account the multi-ethnic nature of the population. Analyses were restricted to a cross-sectional design, and data relied heavily on the accuracy of self-report utilisation on health care services which was subjected to recall bias. Conclusion Depression was found to inflate the total healthcare expenditure among older adults with chronic disease by two-fold. This study provides evidence that there are significant incremental costs associated with depression among the older adults with chronic diseases, demonstrating a need for more resources to improve systematic and clinical care for depressed older adults with chronic diseases.